2022
DOI: 10.3390/antiox11040739
|View full text |Cite
|
Sign up to set email alerts
|

Pholiota nameko Polysaccharides Protect against Ultraviolet A-Induced Photoaging by Regulating Matrix Metalloproteinases in Human Dermal Fibroblasts

Abstract: Ultraviolet-A (UVA) exposure is a major cause of skin aging and can induce oxidative damage and accelerate skin wrinkling. Many natural polysaccharides exhibit a UV protective effect. In research on Pholiota nameko polysaccharides (PNPs), a natural macromolecular polysaccharide (4.4–333.487 kDa), studies have shown that PNPs can significantly decrease elastase activity to protect against UVA-induced aging in Hs68 human dermal fibroblasts. Cellular experiments in the present study indicated that PNPs can protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Excessive ROS can enhance vasodilation and promote the migration of inflammatory cells, leading to tissue damage in the skin [ 60 ]. In addition, ROS can increase tyrosinase expression and cause collagen degradation, thereby resulting in changes in the appearance, such as inflammation, dullness, dehydration, pigmentation, and loss of functionality [ 61 ]. In a previous study, Typha angustifolia polysaccharides obtained through anionic exchange resin showed an evident decrease in fluorescent intensity by 26% at 200 μg/mL, with a PP-3 inhibition rate of 45.3% [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS can enhance vasodilation and promote the migration of inflammatory cells, leading to tissue damage in the skin [ 60 ]. In addition, ROS can increase tyrosinase expression and cause collagen degradation, thereby resulting in changes in the appearance, such as inflammation, dullness, dehydration, pigmentation, and loss of functionality [ 61 ]. In a previous study, Typha angustifolia polysaccharides obtained through anionic exchange resin showed an evident decrease in fluorescent intensity by 26% at 200 μg/mL, with a PP-3 inhibition rate of 45.3% [ 4 ].…”
Section: Discussionmentioning
confidence: 99%